2018
DOI: 10.1097/md.0000000000012899
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of endoscopic ultrasound, computed tomography, magnetic resonance imaging, and endorectal ultrasonography for detecting lymph node involvement in patients with rectal cancer

Abstract: Background:Rectal cancer is one of the most common tumors and is the leading cause of cancer-related deaths in developed countries. Lymph node involvement remains the strongest prognostic factor associated with a worse prognosis in patients with rectal cancer. Several systematic reviews have investigated the accuracy of endoscopic ultrasound, computed tomography, magnetic resonance imaging, and endorectal ultrasonography for lymph node involvement of rectal cancer and compared the diagnostic accuracy of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…The histological classification used in this study was depended on the WHO 2019 classification. A challenge in the identification of nodes with EUS is the inability to visualize nodes that are outside the range of the transducer [ 18 20 ]. Thus, gastric cancer N staging remains an area of uncertainty.…”
Section: Methodsmentioning
confidence: 99%
“…The histological classification used in this study was depended on the WHO 2019 classification. A challenge in the identification of nodes with EUS is the inability to visualize nodes that are outside the range of the transducer [ 18 20 ]. Thus, gastric cancer N staging remains an area of uncertainty.…”
Section: Methodsmentioning
confidence: 99%
“…Challenge in the identification of nodes with EUS is the inability to visualize nodes that are outside the range of the transducer [16][17][18]. Thus, gastric cancer N staging remains to be an area of uncertainty.…”
Section: Data Collectionmentioning
confidence: 99%
“…Risk factors for rectal cancer include Familial Polyposis Syndrome, Diabetes Mellitus, Obesity, Alcohol and Smoking. 1 The most accurate imaging technique to evaluate Positive Circumferential Resection Margin (pCRM) status before Total Mesorectal Excision (TME) is high resolution Magnetic Resonance Imaging (MRI); however, after long course Chemoradiotherapy (CRT) the accuracy of MRI decreases in determining pCRM involvement. Previously some studies showed moderate accuracy of 64-92% in predicting Mesorectal Fascia (MRF) invasion and 33-45% in predicting CRM involvement with post CRT MRI.…”
Section: Introductionmentioning
confidence: 99%